An Analysis of Speech The Presidential Candidates Debate of United States in 2020 - Mac Aditiawarman; Oki Agustriawan (Fakultas Sastra Universitas Ekasakti, 2022)
This research aims to see the impact caused by candidates presidential of United States in 2020 in use of speech acts, where an utterance contains pragmatic meanings to make the listener do what speaker wants through speech, such as statements, orders, offers, thanks and the forms of speech that had have direct effect is like punishing. This analysis is included in pragmatic theory so that it is useful to increase the knowledge of readers from linguistic circles. In speech act theory, this research focuses on the theory based on Austin (1962) then for the illocutionary acts based on Searle (1979). The researcher applies a qualitative description method to collecting data by Djajasudarma (2006), method to analyze data this research applies a pragmatic equivalent method by Sudaryanto (1993), technique to collecting data researcher applies theory of Djajasudarma (2006), including: tapping records, note-taking techniques. The researcher applies technique of analyze data called the determining element sorting technique by Sudaryanto (1993). There are 309 utterances or 100% of a whole data, while illocutionary acts are further grouped into five parts, they are assertive type as many as 184 utterances or equivalent to 59% then directive type as many as 70 utterances or 22%, then the commissive type with 49 utterances or 15%, followed by the expressive type with 5 utterances or 1.6% and the declarative type with at least 1 utterance or about 0.3% and last perlocutionary acts found in this data were 139 or equivalent to 44%.